THE GERMINATION OF INDOGOFERA ZOLLINGERIANA BY SOAKING IN LIQUID SMOKE WITH DIFFERENT CONCENTRATIONS - Yelly Magdalena Mulik; Stormy Vertygo; Vivin E. Se’u; Basry Y. Tang (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2021)
This study aimed to evaluate the effect of immersion using liquid smoke with different concentrations on the germination viability of Indigofera zollingeriana. The design used was a completely randomized design with 4 treatments: A0 = 0% liquid smoke, A20 = 20% liquid smoke, A40 = 40% liquid smoke, A100 = 100% liquid smoke, each treatment with 4 replications. The parameters observed were the germination viability, mean germination time, and mean daily germination. ANOVA analysis showed that the treatment had a significant effect on germination viability but insignificant on the germination rate and mean germination time. Treatment A0 was the treatment with the highest germination viability (75%), but the highest germination rate (0.34 cm/day) was in treatment A20. The higher the concentration of liquid smoke, the lower the germination viability, the germination rate and the mean germination time.